Cystic Fibrosis, Atopy, Asthma and ABPA - Antunes, J (2010)
The role of atopy on cystic fibrosis (CF) progression remains unclear but evidence suggests that it may influence the appearance of co-morbid conditions such as CF asthma or allergic bronchopulmonary aspergillosis (ABPA). Recognising asthma in patients with CF is not always easy but the identification of atopic markers favours the diagnosis. Physicians should be aware of this fact in order to achieve a better control of respiratory symptoms in patients with CF. Bronchial mucosa inflammation and abnormal mucus predispose to mould colonisation. These patients are at higher risk of allergic sensitisation, especially when atopic susceptibility is present. In the particular case of A. fumigatus, allergic sensitisation precedes ABPA development, which occurs in up to 10% of CF patients. Progression of lung function deterioration is most strikingly pronounced in patients with ABPA. Therefore, sensitisation with A. fumigatus should be regularly tested in patients with CF, especially those at higher risk. Recombinant allergens constitute an important advance in differentiating Aspergillus sensitisation from ABPA itself.